Framing in an 1800s Instruction Manual : A Case Study of Frame Markers and Peritext in Frances Lambert’s My Crochet Sampler - Sivén, Oosa (My University, 2026)
This thesis presents a case study examining the frame markers and peritextual elements that are used to frame instructions in Frances Lambert’s My Crochet Sampler. Framing is a rhetorical strategy that is used to promote textual coherence and direct interpretation, and when used effectively, it makes technical writing less unambiguous and more purpose-driven. Framing in the manual is analysed from two perspectives: metadiscoursal and peritextual. To effectively examine these perspectives, Hyland’s interpersonal model and Genette’s theory on peritext are applied to identify elements that possess framing qualities. The analysis extends beyond mere explanation of categories, aiming instead to discover reoccurring patterns and the relationships between metadiscoursal and peritextual framing, which create cohesion within the instructions and direct the learner throughout the learning process. The results of this thesis prove that framing is both textual and visual, and that their usage is interwoven with writer- and period-specific conventions. As this thesis offers only a limited view into some of the cooperating framing methods, further studies are needed to gain a deeper understanding of these discoursal mechanisms in the instructional text type.
Keywords: metadiscourse; peritext; framing; frame markers; crochet; instructions; text type; manuals; nineteenth century